Rice (Oryza) hemoglobins [v2; ref status: indexed, http://f1000r.es/4vp] - Raúl Arredondo-Peter (F1000Research, 2014)
Hemoglobins (Hbs) corresponding to non-symbiotic (nsHb) and truncated (tHb) Hbs have been identified in rice (Oryza). This review discusses the major findings from the current studies on rice Hbs. At the molecular level, a family of the nshb genes, consisting of hb1, hb2, hb3, hb4 and hb5, and a single copy of the thb gene exist in Oryza sativa var. indica and O. sativa var. japonica, Hb transcripts coexist in rice organs and Hb polypeptides exist in rice embryonic and vegetative organs and in the cytoplasm of differentiating cells. At the structural level, the crystal structure of rice Hb1 has been elucidated, and the structures of the other rice Hbs have been modeled. Kinetic analysis indicated that rice Hb1 and 2, and possibly rice Hb3 and 4, exhibit a very high affinity for O2, whereas rice Hb5 and tHb possibly exhibit a low to moderate affinity for O2. Based on the accumulated information on the properties of rice Hbs and data from the analysis of other plant and non-plant Hbs, it is likely that Hbs play a variety of roles in rice organs, including O2-transport, O2-sensing, NO-scavenging and redox-signaling. From an evolutionary perspective, an outline for the evolution of rice Hbs is available. Rice nshb and thb genes vertically evolved through different lineages, rice nsHbs evolved into clade I and clade II lineages and rice nshbs and thbs evolved under the effect of neutral selection. This review also reveals lacunae in our ability to completely understand rice Hbs. Primary lacunae are the absence of experimental information about the precise functions of rice Hbs, the properties of modeled rice Hbs and the cis-elements and trans-acting factors that regulate the expression of rice hb genes, and the partial understanding of the evolution of rice Hbs.